Transition Metal Complexes of Naproxen: Synthesis, Characterization, Forced Degradation Studies, and Analytical Method Verification - Md. Sharif Hasan; Ruhul Kayesh; Farida Begum; S. M. Abdur Rahman (Journal of Analytical Methods in Chemistry)
The aim of our current research was to synthesize some transition metal complexes of Naproxen, determine their physical properties, and examine their relative stability under various conditions. Characterizations of these complexes were done by 1H-NMR, Differential Scanning Calorimetry (DSC), FT-IR, HPLC, and scanning electron microscope (SEM). Complexes were subjected to acidic, basic, and aqueous hydrolysis as well as oxidation, reduction, and thermal degradation. Also the reversed phase high-performance liquid chromatography (RP-HPLC) method of Naproxen outlined in USP was verified for the Naproxen-metal complexes, with respect to accuracy, precision, solution stability, robustness, and system suitability. The melting points of the complexes were higher than that of the parent drug molecule suggesting their thermal stability. In forced degradation study, complexes were found more stable than the Naproxen itself in all conditions: acidic, basic, oxidation, and reduction media. All the HPLC verification parameters were found within the acceptable value. Therefore, it can be concluded from the study that the metal complexes of Naproxen can be more stable drug entity and offer better efficacy and longer shelf life than the parent Naproxen.